2022
DOI: 10.1111/jch.14523
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin association with vascular function in chronic kidney disease

Abstract: Osteocalcin (OCN) is a bone-derived and vitamin K dependent hormone that affects energy metabolism and vascular calcification. The relationship between serum OCN and vascular function in patients with chronic kidney disease (CKD) is uncertain. This study investigated the association between serum OCN and vascular function as expressed with reactive hyperemia index (RHI) and augmentation index (AIx) measured by Endo-PAT 2000 device. This cross-sectional analysis was based on 256 pre-dialysis CKD patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…It was an intriguing finding that the skin microcirculation response (RHR [%]) assessed using the FMSF method, rather than the FMD or RH-PAT responses, was negatively correlated with the duration of TKI's treatment even after adjustment for a patient's age. These results are in line with results from previous studies that assessed age-dependent deterioration of endothelial function using FMD, RH-PAT, or FMSF [39][40][41]. However, when our results were adjusted for patients' age, correlations with FMSF were independent of age whereas correlations with FMD after adjustment were weaker.…”
Section: Discussionsupporting
confidence: 92%
“…It was an intriguing finding that the skin microcirculation response (RHR [%]) assessed using the FMSF method, rather than the FMD or RH-PAT responses, was negatively correlated with the duration of TKI's treatment even after adjustment for a patient's age. These results are in line with results from previous studies that assessed age-dependent deterioration of endothelial function using FMD, RH-PAT, or FMSF [39][40][41]. However, when our results were adjusted for patients' age, correlations with FMSF were independent of age whereas correlations with FMD after adjustment were weaker.…”
Section: Discussionsupporting
confidence: 92%
“…Osteocalcin correlated negatively with renal function in a small study of non-dialysis CKD patients [124], and other investigations have identified a link to cardiovascular risks: a cross-sectional analysis of 256 non-dialysis CKD patients found that low levels of total osteocalcin were associated with endothelial dysfunction, whereas participants with high osteocalcin levels had a greater degree of arterial stiffness [125]. Additionally, a further study focusing on the uncarboxylated form of osteocalcin (ucOC) demonstrated that decreased ucOC levels were closely correlated with subclinical carotid atherosclerosis in non-dialysis CKD patients [126].…”
Section: Osteocalcinmentioning
confidence: 81%
“…Although not directly correlated to vascular calcification, low osteocalcin levels are associated with increased arterial stiffness and carotid atherosclerosis in CKD patients [ 146 , 147 ].…”
Section: Vascular Calcificationmentioning
confidence: 99%